Interactive website: dynamic virtual classroom creation training - Rahmadani (12 Waiheru, 2023)
The integration of Information and Communication Technology (ICT) in teaching in the current era of the industrial revolution opens opportunities to enhance the learning experience and provide a more inclusive, innovative, and engaging education. One of the latest trends receiving attention in the field of education is the implementation of Interactive Websites through the Google Sites platform. Therefore, BDK Ambon, as an educational and training institution, conducts Multimedia Learning Training. In this training, the facilitator, represented by the trainer, conducts research to describe the training process for creating Google Sites as a Learning Portfolio. The research is carried out in Southeast Maluku Regency, involving 35 teachers. This research employs a descriptive survey method divided into three stages: the preparation stage, the implementation stage, and the evaluation stage. The research findings revealed that 90% of the teachers were unfamiliar with how to use Google Sites as a learning portfolio, as observed during the preparation phase. However, during the implementation phase of the training, the participants enthusiastically engaged in the training activities, and by the end of the session, they were capable of creating and utilizing Google Sites to support learning. Moving on to the evaluation phase, the results showed that all participants were categorized above the established standard. The scores of all participants fell into the categories of fairly competent, competent, and highly competent. This demonstrates the effectiveness of multimedia learning training and its ability to provide positive benefits for teachers. Looking ahead, it is necessary to conduct similar training to enable all teachers in the BDK Ambon working area to utilize and leverage technology to its fullest potential.